Pengaruh Tax Knowledge, Tax Socialization dan Business Income terhadap Tax Compliance pada Usaha Mikro, Kecil dan Menengah (UMKM) di Kota Padang - Tia Marsilla; Eka Fauzihardani (Jurnal Eksplorasi Akuntansi, 2023)
Income tax. Most of the tax revenue for Indonesia. MSMEs are a source of the Indonesian economy and are the basis for increasing government tax revenues. Overall, the ratio of formal taxpayer compliance is 67.18 percent, but the ratio of formal taxpayer compliance has not reached the target of 80%. The purpose of this study was to determine the effect of tax knowledge, tax socialization and business income on taxpayer compliance. The focus of this research is the city of Padang which was chosen because it comes from other regions/cities in West Sumatra due to the large number of MSMEs in the city of Padang. This research is a quantitative study using basic data collected through random questionnaires. as many as 400 respondents. The analytical method used in this research is multiple linear analysis. The results of this study indicate that the variables of tax knowledge, tax socialization and business income have a positive effect on MSME taxpayer compliance in the city of Padang. This study is expected to be an evaluation material for the government to further educate the public about taxation, so that the public can also know about taxation and comply with tax regulations in Indonesia through tax socialization.